Stock Market Integration and Corporate Investment in Nigeria: A Critical Analysis - NEJO, Femi MIchael (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Low level of corporate investment in Nigeria coupled with poor financial base of a single stock exchange market system bring the need for the study to critically examined the effect of stock market integration on corporate investment in Nigeria from 1986 to 2022. The study adopted Augmented Dickey Fuller (ADF) unit root test and Auto-regressive Distributed Lag (ARDL). The data used for this study were collected from the Central Bank of Nigeria, Statistical Bulletin (2022). The ADF showed that the real exchange rate, lending interest rate, and trade openness were all integrated of order zero (∆ = 0); while, stock market integration and corporate investment were integrated of order one (∆ = 1). The ADF result showed that stock market integration exhibited a non-stability trend over the years, real exchange rate showed a negative sign but non-significant at 5%; while, lending interest rate and trade openness was negative and significant. The study concluded that stock market integration was volatile over the years which limited the rate of impacting corporate investment in Nigeria; while, lesser interest rate and trade liberation promote corporate investment. The study recommended that in order to fast ease stock market integration, which is crucial for economic progress, the Nigerian Exchange Group NGX should aim toward ensuring that each listed firm on the market have a strong market capitalization through encouraging different ownership structure to possess their respective stock value